Pulmonary Nocardiosis with Aspergillosis in a patient with COPD: A rare co-infection - Durga Shankar Meena; Deepak Kumar; Gopal Krishana Bohra; Mahendra Kumar Garg; Prakrati Yadav; Anuradha Sharma; Kumar S. Abhishek; Pawan Garg; Jaya Pamnani (IDCases, 2020)
Pulmonary Nocardiosis and invasive Aspergillosis are well documented in immunocompromised patients. The coexistence of both infections is a diagnostic rarity, especially in patients with underlying structural lung diseases. We describe this rare association in a 46-year-old female with a history of pulmonary tuberculosis and COPD. The diagnosis of pulmonary Nocardiosis is challenging due to non-specific clinical features, inherent ability to mimic malignancy, tuberculosis and difficulty in the cultivation of the organism. The treating physicians should aware of the rare occurrence of such co-infections in order to prevent misdiagnosis and prompt treatment.